Investigating Spelling Errors among Indonesian EFL Secondary School Students - Muhassin, Mohammad; Hidayah, Renty; Hidayati, Dewi Ayu; Pradana, Satria Adi (English Education: Jurnal Tadris Bahasa Inggris, 2020)
In the Indonesian context, students who learn English face some problems in spelling words. They often make spelling errors in essay writing. This study aims to explore and categorize spelling errors made by Indonesian secondary school students and the primary sources contributing the errors based on Error Analysis (EA) framework. The participants consisted of 38 students chosen from a secondary school in Lampung, Indonesia. The data were obtained from documentation of student’s written essays, and responses in the questionnaire analyzed based on Carney’s (1997) categories of spelling error and Richards’s (1980) types of error sources.  The findings showed that errors under categories of variant, slip, and the split was the most frequently found as the students were mistaken in choosing among the competing letters and sounds and also careless with the correct spelling. Besides, the major error sources were associated with the Indonesian (L1) interference when students transferred their mother tongue to the English (L2) spelling and the inconsistency between English spelling and sounds. The study implies that the learners’ better understanding of L1 and L2’s different systems of spelling as well as pronunciation rules will help them enhance their spelling performance. It is, therefore, suggested that the teachers give students more practice to drill and to pronounce the frequently misspelled words simultaneously to develop their spelling accuracy.